2013
DOI: 10.1016/j.jcv.2013.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside plus nucleotide analogs and cessation of hepatitis B immunoglobulin after liver transplantation in chronic hepatitis B is safe and effective

Abstract: Combined prophylaxis with TDF/ETV nucleoside plus nucleotide analogs and cessation of immunoglobulin after liver transplantation in chronic hepatitis B is safe and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 39 publications
7
34
0
Order By: Relevance
“…None of the patients developed detectable HBV DNA in the serum, and all maintained normal aminotransferase activities. Seroreversion (reappearance of HBsAg) was seen in 7.7 % of patients, which was comparable to those reported in other studies [5][6][7][8][9][10][11][12][13]. Our two patients seroreverted at 7 and 9 months post-OLT, which is also similar time period as previously reported [5][6][7][8][9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…None of the patients developed detectable HBV DNA in the serum, and all maintained normal aminotransferase activities. Seroreversion (reappearance of HBsAg) was seen in 7.7 % of patients, which was comparable to those reported in other studies [5][6][7][8][9][10][11][12][13]. Our two patients seroreverted at 7 and 9 months post-OLT, which is also similar time period as previously reported [5][6][7][8][9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 91%
“…Seroreversion (reappearance of HBsAg) was seen in 7.7 % of patients, which was comparable to those reported in other studies [5][6][7][8][9][10][11][12][13]. Our two patients seroreverted at 7 and 9 months post-OLT, which is also similar time period as previously reported [5][6][7][8][9][10][11][12][13]. In addition, like other patients who seroreverted after switching from HBIg/nucleos(t)ide to dual nucleos(t)ides, our two patients remained HBV DNA negative with normal aminotransferases [5][6][7][8][9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…3,24 However, the introduction of new nucleos(t)ide analogues, including entecavir and tenofovir, in the 2000s, modified the evolution of chronic liver disease caused by HBV. 25,26 A meta-analysis reported that among HBV-negative patients, HBV recurrence rates after OLT did not differ significantly between the group that received prophylaxis following OLT using HBIG + lamivudine and the group that received prophylaxis with entecavir or tenofovir as monotherapy (P = 0.17, risk difference: 0.06, 95% confidence interval [CI]: -0.02 to 0.14).…”
Section: Liver Transplantation and Viral Recurrencementioning
confidence: 99%